Retirement reform in South Africa, Chile, Brazil, and India - Maharaj, Nitosh Krishean (My University, 2018)
The South African government is concerned with the lack of a savings culture in South Africa, particularly, South Africans not saving enough for retirement and thus the need to rely on the social security system. This research article therefore examines South Africa’s social security system and the retirement reforms that the National Treasury has proposed to ensure a better savings culture is created in South Africa. The main aim of this research article was to compare South Africa’s social security and retirement systems to that of Chile, Brazil, and India given the similarities between these countries in terms of social and economic conditions, and to understand the perceptions of the South African professional population in terms of their planning for retirement. The literature review undertaken for the purpose of this research article illustrates that Chile has been at the forefront of retirement reform, having just entered their fourth cycle of reform. As they are known for being the pioneers of the individual accounts system, they have become a key case study for many countries as these countries progress to reform their systems. Through active reforms, Brazil and India have also been successful in reducing their social security debt. Retirement and social security reforms are of global importance as countries forge ahead in trying to achieve social upliftment and sustainability for their citizens. A survey was used as part of the research method, and the purpose of this survey was to develop an understanding of the perceptions of South African’s that are educated and currently working in the corporate world. Twenty-five questions were sent out to the population target, with a specific focus on establishing if they have adequately provisioned for retirement. The study is basic in nature and does not aim to solve the low savings culture in South Africa, but rather to understand the perceptions and relate this to the National Treasury’s efforts to improve South Africans comfort at the time of retirement and old age.
MBA Thesis
Keywords: Retirement income,pension trusts, social security-South Africa